Evaluation of energy metabolism in university students in times of pandemic - Cajahuamán Martinez , Francisco Javier (2022)
The world diet during the Covid-19 pandemic was affected due to unexpected changes in lifestyle and eating habits, being harmful to health,therefore, this work aims to evaluate nutritional consumption, physical activity and body weight influenced by the variation of energy metabolism, before and during the pandemic in university students. The study was observational, descriptive, longitudinal, analytical and prospective. A survey was conducted with a random group of 103 students made up of 60 women and 43 men, whose 71.8% of the sample ranges between 16 and 20 years. The following selection criteria were considered: weight, height and physical activity, then data were collected and classified using statistical tables. The results showed a percentage increase of 5.63% in the general consumption of carbohydrates, proteins and lipids during the pandemic, and 46.60% of the respondents presented hyperphagia, being a possible cause towards obesity and overweight. Finally, it is concluded that there is a change in energy metabolism during the pandemic, associated with various factors such as: physical activity, food intake for carbohydrates, proteins, lipids and lifestyles.